2019
DOI: 10.1037/ppm0000187
|View full text |Cite
|
Sign up to set email alerts
|

Time for a plot twist: Beyond confirmatory approaches to binge-watching research.

Abstract: The advent of the digital age with its progress in digital technology has been associated in recent years with an increase in binge-watching (i.e., seeing multiple episodes of the same TV series in one session). Binge-watching has now become the new normative way to consume TV shows. Nevertheless, along with its recent massive rise has come concerns about the associated mental and physical health outcomes. Currently available results suggest the potential harmfulness and even addictive nature of binge-watching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 64 publications
(142 reference statements)
6
78
0
Order By: Relevance
“…At the same time, however, a second cluster of motivational correlates emerged across studies to make binge-watching appear as something rather compensatory: high levels of bingewatching were associated with the motivations of passing time [32,40], dealing with loneliness [40], and escaping from everyday worries [23,40], while higher frequency was related to procrastination [38*] and emotion regulation [29] purposes. In a similar vein, Flayelle et al [37] found that coping/escapism motivation was specifically linked to problematic binge-watching, thus supporting the hypothesis that problematic binge-watching involves maladaptive coping or emotion-regulation strategies [44]. This line of thinking is in accordance with results showing that problematic involvement in a wide range of recreational activities (e.g., drug use, video gaming, gambling, cybersex) reflects as many different attemps to reduce aversive emotional states [45][46][47].…”
Section: Emerging Profiles Of Binge-watchersmentioning
confidence: 77%
“…At the same time, however, a second cluster of motivational correlates emerged across studies to make binge-watching appear as something rather compensatory: high levels of bingewatching were associated with the motivations of passing time [32,40], dealing with loneliness [40], and escaping from everyday worries [23,40], while higher frequency was related to procrastination [38*] and emotion regulation [29] purposes. In a similar vein, Flayelle et al [37] found that coping/escapism motivation was specifically linked to problematic binge-watching, thus supporting the hypothesis that problematic binge-watching involves maladaptive coping or emotion-regulation strategies [44]. This line of thinking is in accordance with results showing that problematic involvement in a wide range of recreational activities (e.g., drug use, video gaming, gambling, cybersex) reflects as many different attemps to reduce aversive emotional states [45][46][47].…”
Section: Emerging Profiles Of Binge-watchersmentioning
confidence: 77%
“…Consequently, the watching of several episodes of one series in a row has become a popular viewing pattern. Although no empiri-DOI: 10.1159/000506307 cally validated definition exists so far, several authors suggested watching > 2 episodes in one sitting as criterion for binge-watching [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to acknowledge also differences to addictive behaviours. These are, for example, social acceptance, transient overinvolvement, context dependency, and low everyday life impact as outlined by Flayelle et al [6]. These differences are important to consider in order to prevent the overpathologization [12] of a leisure activity often driven by entertainment motivation [13] and not accompanied by any negative consequences for many individuals.…”
Section: Introductionmentioning
confidence: 99%
“…These questionnaires assess two constructs, whose analysis of their relationships is hypothesized to be central in early-stage investigation of binge-watching behaviors (Flayelle, Maurage et al, 2019a;Pittman & Sheehan, 2015;Rubenking & Bracken, 2018;Shim & Kim, 2018;Sung et al, 2018). First, the WTSMQ was developed to assess TV series watching motivations, which are likely key for the understanding of the development and maintenance of binge-watching behaviors (e.g., Uses-and-Gratifications and Selective Exposure theories; Katz, Blumler, & Gurevitch, 1973;Knobloch-Westerwick, 2015;Rubin, 2009;Zillmann & Bryant, 1985).…”
mentioning
confidence: 99%